Anti–N‐methyl‐D‐aspartate‐glutamic‐receptor encephalitis presenting as paroxysmal exercise‐induced foot weakness. Issue 6 (29th May 2013) - Labate, Angelo; Quattrone, Aldo; Dalmau, Josep; Gambardella, Antonio
ABSTRACT Background Patients with anti‐N‐methyl‐D‐aspartate‐glutamic‐receptors (NMDAR) encephalitis often develop complex abnormal movements that may manifest early in the course of illness. Methods/Results A 17‐year‐old boy developed paroxysmal exercise‐induced right foot weakness, without behavioral change. Two weeks later, he had hyperthermia and convulsive status epilepticus. Intravenous valproate resolved the status, but the paroxysmal episodes of right foot weakness persisted. They recurred any time he began running, without any refractory period or other triggering factors. Neurological examination between attacks was normal. Ictal video‐polygraphy showed transient loss of lower limb muscle activity without any EEG changes. Results of brain MRI and extensive laboratory tests were normal. NMDAR antibodies were present in liquor and serum. No tumor was found. He was treated with intravenous methylprednisolone plus immunoglobulins with resolution of his symptoms that have not recurred at 8‐month follow‐up. Conclusions Our case enlarges the spectrum of abnormal movements as presentation of oligosymptomatic anti‐NMDAR encephalitis. © 2013 Movement Disorder Society